Combining ability analysis for seed yield and its components in Indian mustard (Brassica juncea L) (Journal of Oilseed Brassica, 2026)
Ten diverse lines of Indian mustard (Brassica juncea L.) genotypes were crossed in diallel mating design excluding reciprocals to study combining ability. The mean squares due to genotypes including parents, crosses and parents vs. crosses were significant for seed yield/ plant, days to 50% flowering, days to maturity, main raceme length, siliquae on main raceme, siliquae per plant, siliqua length, seeds per siliqua, harvest index. The analysis of variance revealed significant mean sum of squares of general combining ability (GCA) and specific combining ability (SCA) for all the characters. The estimates of GCA effects revealed that parents, viz. NRCDR-02, RH-749, RH-761 and Brijraj were good general combiners for yield contributing traits. The best specific cross combinations for yield and its attributing traits were crosses DRMR IJ-31 × Pusa Bold, DRMR 150-35 × RH-761, DRMR 150-35 × Brijraj, DRMR 150-35 × RH-406, Pusa Bold × JM-2, NRCDR-02 × RH-761, DRMR 1165-40 × Brijraj on the basis of pooled analysis. These F s 1 may be exploited for obtaining transgressive segregants for development of hybrid varieties in Indian mustard